PREFERENSI KONSUMEN TERHADAP BUAH APEL IMPOR DI TOKO BUAH HOKKY DAN PASAR TRADISIONAL AMPEL SURABAYA - Jeani Noviana Rahayu; Elys Fauziyah; Aminah HM Ariyani (Agriekonomika, 2012)
ABSTRACTThis study aimsto describethe characteristics ofconsumers who buy imported apples and analyze the attributes of consumer preferences in buying importedapples.The study was conductedatthe Hokky fruitshopand the Ampel traditional marketing Surabaya. Data analysis was done with descriptive and conjoint methods. The analysis showed that the attributes that a consumer preference in buying apple imports in order are the price, color, texture, size and packaging.Keywords : ConsumerPreference, Attributes, Conjoint